Lessons related to Heavy Metal Pollution through Minamata Case Narrative Study - Endro Tri Susdarwono (Jurnal Pendidikan LLDIKTI Wilayah 1 (JUDIK), 2022)
This study aims to provide an overview or description of learning related to heavy metal pollution through a narrative study of the Minamata case. The research method used in this study is an experimental method, this method is intended to find the relationship of certain variables to other variables under tightly controlled conditions. The characteristics contained in this study include: manipulation, control or control, and observation. The data analysis technique uses the Wilcoxon marked level method to test differences, this method is used to analyze the impact caused by a treatment or stimulus as well as to test the difference in the values ??of two populations represented by two sample groups. This study concludes that the learning method through narrative studies is proven to be able to make students more mastery of materials related to heavy metal pollution. This conclusion is based on several series of hypothesis testing that have been carried out where the alternative hypothesis states that the posttest score of students in the experimental group is greater than the posttest score of students in the control class.